2013
DOI: 10.1007/s10493-013-9717-3
|View full text |Cite
|
Sign up to set email alerts
|

First record of the pantropical blue tick Rhipicephalus microplus in Namibia

Abstract: The invasive pantropical blue tick, Rhipicephalus microplus, has recently been collected from cattle in Namibia. A cross-sectional study aimed at recording the geographic distribution of Rhipicephalus decoloratus and establishing whether R. microplus is present in Namibia was conducted towards the end of summer (March-April) 2013. Ticks were collected from cattle on 18 privately owned farms across a large geographical scale. Ticks were collected from three to five cattle per farm and species belonging to the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…The presence of R. microplus in dry regions has been reported elsewhere in West Africa (Madder et al, 2007), South Africa (Nyangiwe et al, 2013a;Tonnesen et al, 2004), Zambia (Berkvens et al, 1998), East Africa (Lynen et al, 2008) and more recently in Namibia (Nyangiwe et al, 2013b). However, what is noteworthy is the spread of this tick into the interior of the country.…”
Section: Discussionmentioning
confidence: 71%
“…The presence of R. microplus in dry regions has been reported elsewhere in West Africa (Madder et al, 2007), South Africa (Nyangiwe et al, 2013a;Tonnesen et al, 2004), Zambia (Berkvens et al, 1998), East Africa (Lynen et al, 2008) and more recently in Namibia (Nyangiwe et al, 2013b). However, what is noteworthy is the spread of this tick into the interior of the country.…”
Section: Discussionmentioning
confidence: 71%
“…Recent studies have focused on the relationship that exists between this sub-group of the Rhipicephalus species and results have indicated that Rhipicephalus microplus is displacing other ticks of the same genus in West Africa, South Africa, Tanzania, Mozambique and more recently also in Namibia (De Clercq et al, 2012;De Matos et al, 2009;Lynen et al, 2008;Nyangiwe et al, 2013a;Nyangiwe et al, 2013b). In Zimbabwe, Mason and Norval (1980) reported that the exotic R. microplus was displacing the autochthonous Rhipicephalus decoloratus in the eastern parts of the country with unconfirmed reports suggesting that because of the 1980-1983 drought R. microplus could actually have disappeared from the country (Norval et al, 1992), while subsequent research revealed that R. microplus was still limited to the eastern and northern parts of the country (Katsande et al, 1996) and that it could periodically spread into the interior areas of Zimbabwe (Smeenk et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…microplus soon after its first discovery in Ivory Coast and Benin (De Clerq et al, 2012;Madder et al, 2012;Adakal et al, 2013). In South Africa, Nyangiwe et al (2013b) reported on the first record of R. (B.)…”
Section: Acaricide Resistance In Rhipicephalus (Boophilus) Microplus mentioning
confidence: 99%
“…(B.) microplus in New Caledonia, West Africa, South Africa and Namibia and of A. variegatum in the Caribbean through livestock transportation are perfect examples (Madder et al, 2012;Léger et al, 2013;Nyangiwe et al, 2013b;Kamani et al, 2017;Nyangiwe et al, 2017). Rhipicephalus (Boophilus) decoloratus is indigenous and widespread on the African continent (Figure 3), whereas R.…”
Section: Climate Change Human Driving Forces and Tick Distributionmentioning
confidence: 99%